Social integration, physical and mental health and subjective well-being in the floating population—a moderated mediation analysis - Fei, Chengcheng; Zhu, Yiying; Jiang, Longyuan; Zhou, Haixia; Yu, Haiyan (Frontiers in Public Health, 2023)
Background Individuals of domestic migrant populations in China (specifically, migration that is economically driven) often face difficulties in social integration. They are suffering from discrimination and unfair treatment in work and life, which do harm to their physical/mental health and Subjective Well-Being (SWB). Methods The current study utilized a stratified sampling survey in the Yangtze River Delta region of China, in October and November 2022. Six hundred and eleven useful self-reported questionnaires were collected. Questionnaires include questions about social integration, social capital, physical/mental health, and SWB; Bootstrapping method was used to test the mediating effect of physical health and mental health. Multiple hierarchical regression was used to test the moderating effect of social capital. Results Social integration had positive impact on the SWB (r = 0.523, p < 0.01). Bootstrap analysis showed that physical health and mental health partially mediated the correlation between social integration and SWB of Floating Population with a mediation effect of 0.149 and 0.192. Social capital can positively moderate the relationship between two pair of variables: social integration and SWB (β = 0.152, t = 4.42, p < 0.001), physical health and SWB (β = 0.148, t = 4.39, p < 0.01). However, social capital does not play a significant moderating role in the association between the effect of mental health on SWB (β = 0.032, t = 0.973, p > 0.05). Conclusion This study proved a significant correlation between social integration and SWB of Floating Population, with physical/mental health playing a mediating role. Enhancing the social integration of floating population and keeping healthy physically and mentally are key to improving their SWB.